The Effect of Using the C.P.S. Strategy on Developing Creative Problem-Solving Skills among Fine Arts Institute Students in the Medal Course (Journal of the College of Basic Education, 2025)
The research problem was to attempt to answer the following question: "What is the effect of using the C.P.S. strategy on developing creative problem-solving skills among students at the Institute of Fine Arts in the Medallion course?" Therefore, the research aims to identify the strategy's effect on developing students' creative problem-solving skills in the Medallion Art course. The two studies used a quasi-experimental approach. The research sample was selected from female students at the Institute of Fine Arts studying Medallion Art. After preparing the research tools, the experiment was implemented. Using the statistical program SPSS, the results revealed a difference between the students' grades before and after studying the experimental C.P.S. strategy for Medallion Art.The researchers concluded several results, most notably that the strategy had a statistically significant effect on developing creative problem-solving skills in the subject, and that it added cognitive and skill-related improvements to their academic achievement.Based on these results, the researchers recommend:Use the strategy in teaching Medallion Art.Training the institute’s teachers to use the strategy.